Debt Structure Determinants: An empirical comparison between France, Germany and the U.K. - Cordero Domínguez, Verónica (2015)
The paper intends to analyse the determinants of debt structure in firms which headquarters are located in France, Germany and the U.K. It has been proved that there are no only firm-specific features affecting capital structure but also country-specific features, this paper compares the results for three different countries showing there exist differences between them that can be related to country-specific effects.